Privacy preserving search over multiple servers. (2017) - Ibrahim, Ayad; Jin, Hai; Yassin, Ali A.; Zou, Deqing
Search over encrypted data is a hot topic. In this paper, we propose a secure scheme for searching the encrypted servers. Such scheme enables the authorised user to search multiple servers with multi-keyword queries and retrieve the most relevant documents in a descending order with respect to their relevance to the query, without compromising the privacy of his query and the contents of documents he retrieved. In such a setting, each data owner builds his own searchable index, and associates with each document in that index its weight score, which facilitates document ranking. To protect the privacy of these weights, we utilise the privacy preserving mapping (PPM) primitive, while preserving their capability to perform the ranking process. We have conducted several empirical analyses on a real dataset to demonstrate the performance of our proposed scheme.